Comparison of the prognostic values of selected inflammation based scores in patients with medullary thyroid carcinoma: A pilot study. Issue 3 (29th May 2017) - Jiang, Ke; Lei, Jianyong; Li, Canjun; Shu, Kunpeng; Li, Wenbin; Zhang, Yuwei; Li, Zhihui; Gong, Rixiang; Zhu, Jingqiang
Abstract : Background: The significance of inflammation based scores including the neutrophil‐to‐lymphocyte ratio (NLR), derived neutrophil‐to‐lymphocyte ratio (dNLR), platelet‐to‐lymphocyte ratio (PLR), lymphocyte‐to‐monocyte ratio (LMR), prognostic nutritional index (PNI), and plasma fibrinogen remains unclear in medullary thyroid carcinoma (MTC). We aimed to compare the prognostic value of these scores. Methods: Seventy‐eight patients newly diagnosed as MTC with operation in our institution from May 2009 to September 2016 were retrospectively evaluated. Receiver operating characteristic (ROC) curves and Kaplan‐Meier analyses were calculated to compare the prognostic value of these scores. Results: Increased PLR was predictive of lymph node metastasis (AUC = 0.644, P  = 0.022), capsule invasion (AUC = 0.666, P  = 0.007), advanced tumor stages (AUC = 0.657, P  = 0.011), and recurrence (AUC = 0.655, P  = 0.049). Increased fibrinogen was predictive of lymph node metastasis (AUC = 0.669, P  = 0.006) and capsule invasion (AUC = 0.631, P  = 0.038). Reduced PNI was predictive of recurrence (AUC = 0.655, P  = 0.049). Kaplan‐Meier analyses and Cox regression analysis revealed that PLR was a significant predictor for recurrence. Conclusions: PLR, fibrinogen, and PNI are all predictive. Specially, PLR is superior to other inflammation based scores in terms of prognostic ability.